IDENTIFICATION WIDTH OF CHEST AND HIP, AND HEIGHT OF WAIST OF PRIANGAN EWE AT SP3TDK TAMBAK MEKAR SUBANG REGENCY - Gayus Ronald Madison Hutasoit; An an Nurmediansah Suhendri; Siti Nurachma (Fakultas Peternakan, Universitas Padjadjaran, 2022)
Quantitative traits in sheep can provide an overview of livestock productivity in general, and can be used as a basis for selection in efforts to improve genetic quality. Research on “Identification of Chest Width, Hip Width, and Waist Height in Female Priangan Sheep” at the Satuan Pelaksana Pengembangan Perbibitan Ternak Domba Kambing (SP3TDK) Tambak Mekar, Subang Regency, West Java, was held on May 9th until May 13th 2022. The purpose of this study was to determine quantitative traits including chest width, hip width, and waist height in female Priangan Sheep. The method used is descriptive by conducting a census of female Priangan Sheep at SP3TDK Tambak Mekar, Subang Regency with the age group of 6 – 12 months, 12 – 24 months, and over 24 months. The results showed that the female Priangan Sheep in SP3TDK Tambak Mekar, Subang Regency 6 – 12 months of age had an average quantitative traits : chest width 11,00 ± 0,88 centimeter, hip width 11,00 ± 0,84 centimeter, and waist height 48,64 ± 3,45 centimeter; age 12 – 24 months had an average quantitative traits : chest width 13,34 ± 1,25 centimeter, hip width 13,57 ± 1,86 centimeter, and waist height 58,89 ± 4,27 centimeter; and age over 24 had an average quantitative traits : chest width 15,10 ± 1,27 centimeter, hip width 15,63 ± 2,23 centimeter, and waist height 63,29 ± 3,06 centimeter.